Consumers' Evaluations of Genetically Modified Food Messages - Taylor K Ruth; Joy N Rumble (Journal of Applied Communications, 2019)
Consumers are concerned about the risks related to genetically modified (GM) food, and there is a need for agricultural communicators and educators to address those concerns. The purpose of this study was to explore Florida residents’ latitudes of acceptance, rejection, and noncommitment toward GM food messages. The findings from this study can be used to guide communication and education campaigns for GM food. An online survey was distributed to a non-probability sample of 500 Florida residents to fulfill the purpose of the study. The messages that most aligned with the respondents’ views toward GM food discussed how potential risks related to human health had not been adequately investigated and that GM food may be riskier to consume compared to traditional food. The messages that most opposed the respondents’ views were that GM food was safe for consumption and that it caused cancer in humans. People whose views most aligned with the message that GM food caused cancer in humans had the largest latitude of rejection, likely due to their extreme attitude, confirmation bias, and ego-involvement. The largest percentage of respondents accepted messages that aligned with their position but expressed noncommitment to messages that opposed their views. This lack of rejection and indication of alignment with messages related to potential risk and uncertainty indicated Florida consumers were unsure about the effects of GM food. Communicators and educators should acknowledge these concerns when delivering information about GM food to enhance the effectiveness of communication with consumers.
Keywords: genetically modified food; social judgement theory; latitudes of acceptance; attitudes